Comparative phylogeography of two bat species and their mites in Iran shows impact of host sociality and vagility on population structure. (18th November 2021) - Yousefi, Shetav; Sharifi, Mozafar; Štefka, Jan
Abstract: Parasite species lacking a free‐living stage rely on their hosts for dispersal. Their population genetic structure depends on the host's vagility and dispersal rate. To gain more insight into the drivers responsible for shaping the spatio‐temporal population structure in host–parasite systems, we used mitochondrial DNA sequences to compare patterns of genetic diversity in two closely related and contact‐transmitted parasitic wing mites Spinturnix psi and S .  myoti with their bat hosts Miniopterus pallidus and Myotis blythii, respectively, across vast distances in Iran. We observed almost no genetic differentiation between mites living on bats in different colonies even from distant locations, whereas we found some level of genetic differentiation and isolation by distance in each host species, particularly in the less vagrant M .  blythii . Despite Iran's high spatial divergence and long distance between the sampled locations, local genetic diversity and inter‐population gene flow in the parasites were high, even between different sides of the Zagros and Alborz Mountains. The genetic similarity that was observed among mite populations likely reflects genetic exchanges between colonies at swarming places of bats, as well as the possible occupation of other host species, resulting in a higher effective population size and more dispersal opportunities for the mites.